2000
DOI: 10.1021/bi0007223
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Spectroscopy of Single Tryptophan Mutants of Apolipophorin-III in Discoidal Lipoproteins of Dimyristoylphosphatidylcholine

Abstract: The structure of the exchangeable apolipoprotein, apolipophorin-III from Locusta migratoria, apoLp-III, is described as a bundle of five amphipathic alpha-helices. To study the interaction of each of the helices of apoLp-III with a lipid surface, we designed five single-Trp mutants, each containing a Trp residue in a different alpha-helix. The Trp residues were located in the nonpolar domains of the amphipathic alpha-helices. The kinetics of the spontaneous interaction of the mutants with dimyristoylphosphatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
(49 reference statements)
3
13
0
Order By: Relevance
“…Thus, a fully extended polypeptide chain would produce essentially the same results that were observed in this study. In fact, on the basis of the results of this study as well as on the conclusions of recent studies reporting on the topology and lipid-interacting regions of the apolipoprotein (17,18), a structural model of apoLp-III in discoidal lipoproteins is proposed below. In this model it is assumed that the apolipoprotein adopts a fully extended helical conformation.…”
Section: Conformation Of Apolp-iii In the Lipid-bound State Inferred mentioning
confidence: 76%
See 1 more Smart Citation
“…Thus, a fully extended polypeptide chain would produce essentially the same results that were observed in this study. In fact, on the basis of the results of this study as well as on the conclusions of recent studies reporting on the topology and lipid-interacting regions of the apolipoprotein (17,18), a structural model of apoLp-III in discoidal lipoproteins is proposed below. In this model it is assumed that the apolipoprotein adopts a fully extended helical conformation.…”
Section: Conformation Of Apolp-iii In the Lipid-bound State Inferred mentioning
confidence: 76%
“…The first of these studies, which used water-soluble quenchers, suggested that at least three of the five ␣-helices (helices 1, 4, and 5) interact with the lipid surface (17). The second study, which used lipid quenchers, suggested that in discoidal lipoproteins all ␣-helices of apoLp-III interact with the phospholipid acyl chains (18).…”
Section: Discussionmentioning
confidence: 99%
“…Protein Expression and Purification-Thioredoxin-apoLp-III fusion proteins were overexpressed and isolated from the bacteria as previously reported (13,14). The fusion proteins were purified by standard nickel affinity chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…Steady-state fluorescence studies showed a strong change in the properties of tryptophan (L. migratoria) or tyrosine (M. sexta) upon binding to DMPC, indicative of their transition to a lipid environment Narayanaswami et al, 1996a;Weers et al, 2000b). This transition was observed for each helix (Soulages and Arrese, 2000). Near and Far UV CD analysis showed dramatic changes in spectra upon lipid binding, indicative of a large conformational change (Weers et al, 1994).…”
Section: Lipid-bound Conformationmentioning
confidence: 99%